CT perfusion in the diagnosis of pyelonephritis: advantages and disadvantages. A review - Valentin c Pavlov; Vladimir A. Vorobev; Vladimir A. Ananiev (Consilium Medicum)
Acute suppurative pyelonephritis is a severe kidney infection characterized by areas of ischemia and necrosis, making accurate assessment of renal perfusion crucial for diagnosis and treatment. In recent years, modern functional imaging techniques, including perfusion computed tomography (CT perfusion), have been increasingly used to evaluate renal blood flow. This review presents current data on the capabilities of renal CT perfusion in diagnosing and monitoring acute suppurative pyelonephritis, describing the principles of the technique and data post-processing for quantitative hemodynamic measurements. The CT perfusion method helps identify ischemic areas in the affected kidney and provides an objective assessment of perfusion impairment. Clinical studies show that perfusion abnormalities correlate with disease severity and the occurrence of suppurative complications, supporting the use of CT perfusion as an important prognostic tool for selecting optimal conservative or surgical treatment. Several advantages of CT perfusion are highlighted, such as high diagnostic value due to combined morphological and functional assessment, short examination time, and the ability to simultaneously assess both kidneys for comparison. However, the method also has significant limitations: high radiation exposure and the need for intravenous contrast increase the risk of complications (e.g., contrast-induced nephropathy) and restrict its use in patients with renal insufficiency. To mitigate these risks, careful patient selection, minimal necessary doses of radiation and contrast, and adequate hydration are recommended. Thus, renal CT perfusion is a promising adjunct in the diagnosis of acute pyelonephritis, capable of improving the assessment of pathological changes and patient outcomes when used judiciously.